Target cost tool to achieve competitive advantage - محمد سعاد جاسم (Journal of Economics and Administrative Sciences, 2011)
Target costing is one of the modern techniques in strategic Management accounting, Is has shown active adoption to changes in current business environments, In addition, is has seen a growth in strategic approach, The goal of using target costing is to build and strengthen competition abilities of economic units through introducing appropriate ways to decrease cost values while maintaining and improving quality of product, So this study is aim to show how can economic units use target costing to achieve competitive advantages .